Stable isotope signatures of soil nitrogen on an environmental–geomorphic gradient within the Congo Basin - S. Baumgartner; S. Baumgartner; M. Bauters; M. Bauters; M. Barthel; T. W. Drake; L. C. Ntaboba; B. M. Bazirake; J. Six; P. Boeckx; K. Van Oost (SOIL, 2021)
Nitrogen (N) availability can be highly variable in tropical forests on regional and local scales. While environmental gradients influence N cycling on a regional scale, topography is known to affect N availability on a local scale. We compared natural abundance of 15N isotopes of soil profiles in tropical lowland forest, tropical montane forest, and subtropical Miombo woodland within the Congo Basin as a proxy to assess ecosystem-level differences in N cycling. Soil δ15N profiles indicated that N cycling in the montane forest is relatively more closed and dominated by organic N turnover, whereas the lowland forest and Miombo woodland experienced a more open N cycle dominated by inorganic N. Furthermore, we examined the effect of slope gradient on soil δ15N within forest types to quantify local differences induced by topography. Our results show that slope gradient only affects the soil δ15N in the Miombo forest, which is prone to erosion due to a lower vegetation cover and intense rainfall at the onset of the wet season. Lowland forest, on the other hand, with a flat topography and protective vegetation cover, showed no influence of topography on soil δ15N in our study site. Despite the steep topography, slope angles do not affect soil δ15N in the montane forest, although stable isotope signatures exhibited higher variability within this ecosystem. A pan-tropical analysis of soil δ15N values (i.e., from our study and literature) reveals that soil δ15N in tropical forests is best explained by factors controlling erosion, namely mean annual precipitation, leaf area index, and slope gradient. Erosive forces vary immensely between different tropical forest ecosystems, and our results highlight the need for more spatial coverage of N cycling studies in tropical forests, to further elucidate the local impact of topography on N cycling in this biome.